2016
DOI: 10.1002/cncr.30083
|View full text |Cite
|
Sign up to set email alerts
|

Second‐opinion interpretations of neuroimaging studies by oncologic neuroradiologists can help reduce errors in cancer care

Abstract: Background The purpose of this study was to investigate the utility and clinical impact of second-opinion interpretations of outside neuroimaging studies by oncologic neuroradiologists at an NCI-designated cancer center. Methods We performed a retrospective analysis of initial outside and second-opinion radiology reports from 300 CT and MRI neuroimaging studies and identified cases with discrepancies between the two reports. An adult neuro-oncologist, pediatric neuro-oncologist, and head and neck surgeon rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…By 2012, that number had increased to 1,157, and in 2015, 2,053 second opinion reviews of FDG PET/CT scans were performed. Several studies have suggested that subspecialty review of body CT, neuroradiology, and mammography exams have varying levels of benefit, with discrepancy rates between the initial report and the specialist reassessment ranging between 1 and 19% [18]. The value of subspecialist review of FDG PET/CT scans is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…By 2012, that number had increased to 1,157, and in 2015, 2,053 second opinion reviews of FDG PET/CT scans were performed. Several studies have suggested that subspecialty review of body CT, neuroradiology, and mammography exams have varying levels of benefit, with discrepancy rates between the initial report and the specialist reassessment ranging between 1 and 19% [18]. The value of subspecialist review of FDG PET/CT scans is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we set out to expand on this prior scholarship to develop methodology for measuring not just a radiologist's area of work focus, but also whether advanced imaging is interpreted by a high-volume reader in the field. We present here this methodology and apply it to neurological MRI and musculoskeletal MRI, two areas in which specialist interpretations have been demonstrated to add value [3,4,6,9].…”
Section: Prior Work By Rosenkrantz Et Al Uses This Cms Data To Classimentioning
confidence: 99%
“…Specialization within radiology can take the form of either advanced training, or a increased focus or volume of one's work within a subfield. Both of these forms of specialization have been shown to result in increased diagnostic performance [3][4][5][6][7][8][9][10][11][12][13][14]. While the value of specialization has been demonstrated across a variety of radiology subfields, including musculoskeletal, neurologic, abdominopelvic, thoracic, and breast imaging, the greatest impact has been largely for more complex imaging tasks, such as MRI or oncologic imaging.…”
Section: Introductionmentioning
confidence: 99%
“…radiologists specializing in cancer imaging, with secondopinion reports indicating the need for changes in patient management in as many as 13% to 53.5% of cases. [7][8][9][10][11][12][13][14][15][16][17][18][19] Second-opinion review can prevent unnecessary biopsies while improving cancer detection, as was shown by a recent study that included 147 patients who self-referred for second-opinion readings of breast images. 20 On secondary review, 24 (25%) of 96 lesions originally reported as suspicious were downgraded to benign or probably benign, preventing biopsy in 21 patients, all of whom remained disease free on follow-up imaging.…”
Section: © 2019 By American Society Of Clinical Oncologymentioning
confidence: 99%